2002
DOI: 10.1074/jbc.m112303200
|View full text |Cite
|
Sign up to set email alerts
|

Chronic Treatment with Azide in Situ Leads to an Irreversible Loss of Cytochrome c Oxidase Activity via Holoenzyme Dissociation

Abstract: Chronic treatment of cultured cells with very low levels of azide (I 50 <10 M) leads to slow (t1 ⁄2 ‫؍‬ 6 h), irreversible loss of cytochrome c oxidase (COX) activity. Azidemediated COX losses were not accompanied by inhibition of other mitochondrial enzymes and were not dependent upon electron flux through oxidative phosphorylation. Although azide treatment also reduced activity (but not content) of both CuZn superoxide dismutase and catalase, a spectrum of pro-oxidants (and anti-oxidants) failed to mimic (or… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
75
0

Year Published

2004
2004
2019
2019

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 78 publications
(76 citation statements)
references
References 64 publications
(55 reference statements)
1
75
0
Order By: Relevance
“…For all further experiments, azide concentrations of 50 and 75 M were used. Previous studies have demonstrated that, at micromolar concentrations of azide, the activity of cytochrome c oxidase (COX) is specifically reduced without affecting either mRNA or protein expression levels of COX or the activity of other mitochondrial enzymes (14,15). Assessment of cell viability by trypan blue exclusion also demonstrated that, in this study, treatment with micromolar concen-trations of azide did not have a detrimental effect on cell viability.…”
Section: Measurement Of Cellular Respiratory Chain Function In Azidetsupporting
confidence: 49%
See 1 more Smart Citation
“…For all further experiments, azide concentrations of 50 and 75 M were used. Previous studies have demonstrated that, at micromolar concentrations of azide, the activity of cytochrome c oxidase (COX) is specifically reduced without affecting either mRNA or protein expression levels of COX or the activity of other mitochondrial enzymes (14,15). Assessment of cell viability by trypan blue exclusion also demonstrated that, in this study, treatment with micromolar concen-trations of azide did not have a detrimental effect on cell viability.…”
Section: Measurement Of Cellular Respiratory Chain Function In Azidetsupporting
confidence: 49%
“…To address this specific question, we studied insulin action in primary human skeletal muscle cultures and titrated the concentration of azide, a specific inhibitor of cytochrome c oxidase (complex IV) in the mitochondrial respiratory chain (14,15), to regulate the degree of suppression of mitochondrial respiration.…”
mentioning
confidence: 99%
“…30 It is well established that NaN 3 is a good quencher of singlet oxygen. Quenching rate constants, k q , over the range ~ 3-6 × 10 8 s -1 M -1 have been reported for experiments performed in aqueous systems, and a value as large as 5 × 10 9 s -1 M -1 has been reported for CH 3 CN.…”
Section: Singlet Oxygen Quenching By Sodium Azide In Sucrose Solutionmentioning
confidence: 99%
“…We investigated how myogenesis was affected by the inhibition of mitochondrial activity or by glucose deprivation. NaN 3 can irreversibly inhibit cytochrome c oxidase (50% inhibitory concentration, Ͻ10 M) in C2C12 cells (31), thus blocking the oxidative phosphorylation in mitochondria. However, myogenic differentiation of C2C12 myoblasts did not change significantly when chronically treated with 100 M NaN 3 in the presence of 4.5 g of glucose per liter (Fig.…”
Section: Myogenesis Under Hypoxiamentioning
confidence: 99%